126 Safety and effectiveness of acute heart failure care as outpatient (safe): a meta-analysis of studies comparing outpatient based management with standard inpatient care. (6th June 2022) - Bahar, Jameela; Rahman, Amna; Wong, GWY; Sankaranarayanan, Rajiv; Ahmed, Fozia; Taylor, Rebecca; Fuat, Ahmet; Squire, Ian; Cleland, John; Lip, Gregory; Gamble, James; Joseph, Prince Josiah; et al.
Abstract : Introduction: Patients with acutely decompensated heart failure (ADHF) are usually admitted to hospital for management. However, there is growing interest in delivering IV diuretic therapy at home, in the community or in hospital day-care units. The safety and effectiveness of out-patient based management (OPM) for ADHF has not been established. Accordingly, we conducted a systematic literature review and meta-analysis to investigate the safety and efficacy of OPM compared to in-patient management (IPM) of ADHF. Methods: A systematic literature review and meta-analysis. Pre-specified endpoints were 30-day mortality and 30-day hospitalisation. The meta-analysis was conducted using RevMan 5.4 software. Results: 29 studies of OPM were identified. Only 5 directly compared OPM with IPM -including 3 observational studies [1–3], and two randomised controlled trials (RCTs) [4–5]. In the 5 papers comparing IPM vs OPM, the mean age of the IPM cohort was 77 (compared with 75 in OPM), with a similar proportion of male patients (55.5 v 55.6%). In the study-level aggregate analysis, 30-day all-cause mortality was 9.3% (121/1303) for OPM, compared with 15.6% (320/2047) for IPM (OR 0.29[0.09, 0.93] p=0.04) [Fig. 1]. Four studies reported 30-day all-cause hospitalisation; 22.0% for IPM vs 16.8% for OPM (OR 0.73 [95% CI 0.61, 0.89], p=0.001) [Fig. 2] However, in the 2 RCTs, we found no difference in 30-day mortality or hospitalisation. Overall risk of bias was low in the trials [Table 1]. Conclusion: In observational studies, OPM of ADHF is associated with lower 30-day re-hospitalisation and lower 30-day mortality. Such differences were not observed in two small single-centre RCTs. A substantial multicentre RCT is required to confirm the safety and efficacy of OPM for ADHF. References: 1. Thomas K et al. Ambulatory management of patients with acute heart failure: Setting up a multi-disciplinary service. Presented in British Society of Heart Failure Meeting 2019. 2. Salmon TE et al. Long Term Outcomes of Ambulatory Outpatient Management of Acute decompensated Heart Failure in a Heart Failure specialist Nurse Delivered Specialist Unit Versus Inpatient Management. Circ Suppl . 2021; Vol 144, Issue Suppl_1 1. Ahmed FZ et al . Ambulatory intravenous furosemide for decompensated heart failure: safe, feasible, and effective. ESC Heart Fail . 2021;8 (5):3906–16. 4. Wong K et al . Does outpatient based IV diuretic treatment for acute heart failure give patients hope? Heart 2021;107 :A116-A117. 5. Hamo CE et al . OUTpatient intravenous LASix Trial in reducing hospitalization for acute decompensated heart failure (OUTLAST). PLoS One . 2021;16 (6):e0253014. Conflict of Interest: None